The Effectiveness of Village Government Service in the Lebu Digital Program - Azzahra, Septiyani; Putri, Amelia Regita Cahyani; Permana, Ipik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to evaluate the effectiveness of village government services under the Lebu Digital Program in Cangkingan Village, Kedokanbunder District, Indramayu Regency. This program is an innovation in digitalizing village public services through a website-based Village Information System (SID). The results show that this program facilitates public access to administrative services, village information, and budget transparency, while accelerating the service process. However, challenges faced include limited human resources, lack of community digital literacy, inadequate infrastructure, and limited budget. Improvements are made through training, increasing digital literacy, and optimizing funds and facilities. Overall, this program has had a positive impact on the effectiveness of village government services.